2010
DOI: 10.1371/journal.pmed.1000289
|View full text |Cite
|
Sign up to set email alerts
|

Gestational Age at Delivery and Special Educational Need: Retrospective Cohort Study of 407,503 Schoolchildren

Abstract: A retrospective cohort study of 407,503 schoolchildren by Jill Pell and colleagues finds that gestational age at delivery has a dose-dependent relationship with the risk of special educational needs that extends across the full gestational range.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

29
372
3
9

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 391 publications
(413 citation statements)
references
References 19 publications
29
372
3
9
Order By: Relevance
“…It has previously been reported that the relationship between gestational age and academic outcomes is not linear but curvilinear with increasingly stronger effects below 33-36 weeks [25,35,44, 45] thus we explored this possibility. Results, however, showed that effects of preterm birth on early inhibition and effects of inhibition on later outcomes were overall not stronger in the more preterm compared with the term groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has previously been reported that the relationship between gestational age and academic outcomes is not linear but curvilinear with increasingly stronger effects below 33-36 weeks [25,35,44, 45] thus we explored this possibility. Results, however, showed that effects of preterm birth on early inhibition and effects of inhibition on later outcomes were overall not stronger in the more preterm compared with the term groups.…”
Section: Discussionmentioning
confidence: 99%
“…Gestational age at birth was determined from maternal reports of the last menstrual period and serial ultrasounds during pregnancy. Children were summarized into five GA groups (very preterm: <32 weeks GA; moderately preterm: 32-33 weeks GA; late preterm: 34-36 weeks GA; early term: 37-38 weeks GA; full term 39-41 weeks GA) in order to make findings comparable to other studies [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…In addition, its benefits may be offset by longer-term adverse outcomes in children because of delivery at "early-term" gestation (37 to 39 weeks). [11][12][13][14] Some obstetricians in the United Kingdom already induce labor at the due date (40 weeks of gestation); rates of induction are 39% among women 40 to 44 years of age and 58% among women 45 years of age or older. Among obstetricians who do not induce labor in older pregnant women at the due date, one third are reluctant to offer induction because they are concerned about increasing the likelihood of cesarean delivery, even though they think that induction would improve perinatal outcomes.…”
mentioning
confidence: 99%
“…c hildren born very preterm (<32 wk gestation) are at high risk for adverse cognitive outcomes including intellectual disability, learning difficulties, and special educational needs (1,2). In particular, very preterm children have substantial difficulties with mathematics that are not accounted for by low intelligence (IQ) (see ref.…”
mentioning
confidence: 99%